Pollen development and anther morphology in 14 species of Rhamnaceae - Gotelli, Marina María (2016)
Microsporogenesis, microgametogenesis, and anther structure of 14 species belonging to Rhamneae (Rhamnoids clade), Paliureae, Pomaderreae, Colletieae, and Gouanieae (Ziziphoids clade) of the Rhamnaceae family were analyzed using bright-field, scanning, and transmission electron microscopy. The aim is to look for morphological characters that have systematic value on a suprageneric level within the family. The character states of the number of nuclei in tapetal cells, the endothecial thickening pattern, and the number of endothecial layers are consistent on tribal level. Tribes were previously delineated based on molecular phylogenetic evidence. On the other hand, pollen morphology does not seem to have systematic value at tribal level in Rhamnaceae. The presence or absence of orbicules and their morphology vary within tribes. It seems that for Rhamnaceae, the anatomy of the reproductive sporophytic structures could have more systematic value than the gametophytic structures. However, more studies are needed to confirm this.